Photographic Atlas of Auroral Forms Observed at Syowa Station (AERONOMY) - KANEDA, Eisuke; OGUTI, Takasi; NAGATA, Takesi (1968)
P(論文) Auroral forms observed at Syowa Station, Antarctica, are compiled in the form of an atlas. A revised system of classification is used which relates auroral displays to physical mechanisms. Classification is conducted under the following headings 1) Horizontal Extension, 2) Form of the Lower Border, 3) Homogeneity, 4) Vertical Profile, 5) Brightness, 6) Colour, 7) Activity and 8) Aspect. departmental bulletin paper